PANCASILA, DEMOCRACY, AND NKRI BER-SHARĪ’AH IN INDONESIA: HOW CHRISTIANS SHOULD RESPOND AND PARTICIPATE - Andreas Jonathan (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2020)
Democracy, pluralism, Pancasila, and religious freedom become a heated debate in Indonesia because they arenot only theoretical and conceptual but also have a significant influence on many aspects of the nation’s life.Moreover, the demand for the implementation of sharī’ah from a small number of Muslim groups continues toechoe in this country which, off course, concern also the Christians who become the second largest populationin this country. This paper is an attempt to examine the Christians’ participation in democracy and Pancasilaamids the demand for the implementation of sharī’ah in Indonesia. It discusses theological perspectives forChristians’ participation in the public space, a brief history of the struggle on sharī’ah law and Pancasila, andhow Christians have and should respond through civil society. The paper argues that Christians can participatein many ways in democratization and defending Pancasila in Indonesia through the channels of civil society.